SUSCEPTIBILITY OF SOME HARD AND SOFT WHEAT CULTIVARS FOR COVERED SMUT AND ITS CONTROL - M.S. Hassan (Mesopotamia Journal of Agriculture)
An experiment conducted at College of Agriculture, Univ. of Baghdad during seaso 2006 to evaluate susceptibility of some hard and soft wheat cultivars for covered smut caused by Tilletia spp. Results showed high resistance of C.Vs. Tamuz 2 , Iratum and Durum wheat C.Vs., Umrabi, Sham 3, and Aksad under artificial inoculation , while Latifia, SaberBeg and Milad showed high susceptibility toward this infection. Water Agar and Corn Meal Agar media gave the highest spore germination in the laboratory. Most of the chemical fungicides and organic substances were more effective against this disease particularly Carboxin and Vitvax-plus which prevented spores germination completely on W.A. with no effects on the grain viability. Field trials showed significant effects of Dividen, Raxil and Vitvax-plus with complete reduction of disease in Sali cultivar 98.3% and 96.6% in SaberBeg respectively. Carboxin reduced infections by 97.3% in Sali and 98.2% in SaberBeg. Wheat flour treatment also reduced disease incidence in both Sali and SaberBeg by 90.8 and 88.3% respectively compared with 84.3% and 74.0% used skim milk in Sali and SaberBeg respectively. Finally Chemofoom application reduced infected plants by 80.3% in SaberBeg , cultivars.